An Analysis on the English-Speaking Anxiety of the First Semester Students of Aquatic Resource Management Study Program - Armita Permatasari (LP. Ma'arif Janggan Magetan, 2023)
This study aimed at finding out the factors that causing student’s’ anxiety in English speaking and the types of student’s’ anxiety in English speaking. This research employed descriptive-qualitative method. The population of this research consisted of 196 the first semester students of Agricultural faculty at Universitas Muhammadiyah Sinjai. This research used purposive sampling technique in choosing sample; the sample of this study was 15 students of Aquatic Resources Management study program Agricultural faculty. The researcher used observation checklist, open-ended questionnaire and interview in collecting data. The result of this study showed that there are five factors that causing students’ anxiety in speaking English, the first factor that mostly provoking students to be anxiety is afraid of making mistake when the students have perception about their low ability in English proficiency and afraid to going wrong in their performance. The second factor was lack of vocabulary. The third was lack of confidence. Most of students anxious because they were un-confident of their ability in speaking. The fourth was friends/classmates. The types of anxiety that students experienced in their speaking performance, the most type of anxiety was test anxiety. The second was communication apprehension and the lowest was fear of negative evaluation. Furthermore, the lecturer of speaking must recognize the anxious students and give treatment based on their types of anxiety.